To compare the functions \( f(x) = x^3 + 1 \) and \( g(x) = x + 1 \) based on their intercepts, let's first identify the intercepts for each function:
For \( f(x) = x^3 + 1 \):
-
Y-intercept: This occurs when \( x = 0 \): \[ f(0) = 0^3 + 1 = 1 \implies \text{Y-intercept is } (0, 1). \]
-
X-intercept: This occurs when \( f(x) = 0 \): \[ x^3 + 1 = 0 \implies x^3 = -1 \implies x = -1 \implies \text{X-intercept is } (-1, 0). \]
For \( g(x) = x + 1 \):
-
Y-intercept: This occurs when \( x = 0 \): \[ g(0) = 0 + 1 = 1 \implies \text{Y-intercept is } (0, 1). \]
-
X-intercept: This occurs when \( g(x) = 0 \): \[ x + 1 = 0 \implies x = -1 \implies \text{X-intercept is } (-1, 0). \]
Summary of intercepts:
- Both functions have a Y-intercept of \( (0, 1) \).
- Both functions have an X-intercept of \( (-1, 0) \).
Now, let's evaluate the options provided:
-
Both functions have a y-intercept of (−1,0) and an x-intercept of (0,1).
- Incorrect.
-
Both functions have a y-intercept of (−1,0) and an x-intercept of (0,1).
- Incorrect.
-
The graphs intersect at (1,2).
- This is true for \( f(1) \) but not for \( g(1) \), not a statement about intercepts but about points.
-
The graphs intersect at (1,2).
- Repeated statement, same as above.
-
The x- and y-intercepts are different for each function.
- Incorrect, they are the same as shown.
-
Both functions have an x-intercept of (−1,0) and a y-intercept of (0,1).
- Correct.
Thus, the correct response is: Both functions have an x-intercept of (−1,0) and a y-intercept of (0,1).